Tingkat Pengetahuan Dan Motivasi Perawat Dengan Kepatuhan Melakukan Five Moments Hand Hygiene Di RSUD Sayang Kab. Cianjur - Shinta Arini Ayu; Tri Kesuma Dewi; Cecep Juhana (Malahayati Nursing Journal, 2022)
ABSTRACT Five moment hand hygiene is an early step in preventation of Hospital Acquired Infection (HAIs), which there are factors that can affect them, there are the knowledge and motivation. Good knowledge and great motivation be strong to hold to reduce the transmission of infection through hand hygiene and compliance to do Five moment hand hygiene. Purpose of this research was to identify the relation of knowledge and motivation nurses in compliance five moment hand hygiene at The General Hospital (RSUD) Sayang, Cianjur Regency.  The research design using the layout of analytic study of the correlation with cross-sectional approach. Sampling using Probability Sampling with Proportional Stratified Random Sampling approach. The primary data obtained from questionnaire sheet and result of observation. The sample in this research amounted 92 respondents with the time span of October 2021 – January 2022 and did in Emergency Departments (IGD),VIP, Adult Inpatient and Children Inpatient at The General Hospital (RSUD) Sayang, Cianjur Regency. Analysis using the statistical test of the correlation of spearman rho with the level of significance (α)≤0,05, indicates no relation between level of knowledge nurses with compliance five moments hand hygiene (Ƥ =0,158) and show there is a relation between motivation nurses with compliance five moments hand hygiene (Ƥ =0,009) at The General Hospital (RSUD) Sayang, Cianjur Regency. The motivation needed nurses to comply of five moment hand hygiene. Supervision and training is expected to increase the motivation of nurses in the prevention and control of nosocomial infections. Keywords: Knowledge, Motivation, Compliance, Hand hygiene, Five Moment Hand Hygiene  ABSTRAKFive moment hand hygiene merupakan langkah awal pencegahan Hospital Acquired Infection (HAIs), dimana ada faktor yang dapat mempengaruhi diantara nya adalah pengetahuan dan motivasi. Pengetahuan yang baik dan motivasi yang besar menjadi pegangan yang kuat untuk mengurangi penularan infeksi melalui hand hygiene dan kepatuhan pelaksanaan Five moment hand hygiene. Tujuan dari penelitian ini adalah untuk mengidentifikasi hubungan pengetahuan dan motivasi perawat terhadap kepatuhan five moment hand hygiene di RSUD Sayang Kab. Cianjur. Desain penelitian yang digunakan adalah rancangan penelitian analitik korelasi dengan pendekatan croos-sectional. Sampling menggunakan Probability Sampling dengan pendekatan Proportional Stratified Random Sampling. Data primer didapatkan dari lembar kuesioner dan hasil observasi. Sample dalam penelitian ini berjumlah 92 responden dengan rentang waktu Oktober 2021 – Januari 2022 dan dilakukan diruang IGD, VIP, Rawat Inap Dewasa dan Rawat Inap Anak RSUD Sayang Kab. Cianjur. Analisa menggunakan uji statistic korelasi dari spearman rho dengan tingkat kemaknaan (α)≤0,05, menunjukkan tidak ada hubungan antara tingkat pengetahuan perawat dengan kepatuhan five moments hand hygiene (Ƥ =0,158) dan ada hubungan antara motivasi perawat dengan kepatuhan five moments hand hygiene (Ƥ =0,009) di RSUD Sayang Cianjur. Motivasi dibutuhkan perawat agar patuh terhadap five moment hand hygiene. Supervisi dan pelatihan diharapkan dapat meningkatkan motivasi perawat dalam pencegahan dan mengendalikan infeksi nosokomial. Kata kunci: Pengetahuan, Motivasi, Kepatuhan, Hand hygiene, Five Moment Hand Hygiene